Flexible ethanol production: Energy from sugarcane bagasse might help the sustainability of biofuels - Shibuya, Marcelo Kenji; de Alencar Näas, Irenilza; Neto, Mario Mollo [UNESP] (Springer Nature, 2015)
The ethanol industry in Brazil is going through a period of stagnation, resulting in the reduction of ethanol supply. The ethanol for automotive purposes may be anhydrous, which is used as an anti-detonating additive to gasoline; and hydrated ethanol, which can be used in the flex-fuel vehicles, which can use the biofuel, gasoline or a mixture of both in any proportion. This study is aimed to analyze the contribution that energy from the sugarcane bagasse could bring to the production of corn ethanol in plants adapted to operate with both sugarcane and the cereal. Therefore, it was considered, the surplus energy from sugarcane biomass and maize availability in the producing region. At the end of the article, the results are discussed by providing an analysis of the application of corn as alternative raw material for the production of ethanol in Brazil.
Keywords: Biofuel; Energy efficiency; Ethanol